Experimental study of large-sized concrete filled steel tube columns under blast load. (1st March 2017) - Wang, Hongwei; Wu, Chengqing; Zhang, Fangrui; Fang, Qin; Xiang, Hengbo; Li, Peng; Li, Zhibin; Zhou, Yun; Zhang, Yadong; Li, Jun
Highlights: Concrete-filled steel tube (CFST) columns are tested under close-range blasts. The influence from charge weight, tube thickness and cross section geometry was analyzed. Failure modes of CFST columns under blast loads were studied. Residual strength of blast-damaged CFST columns was analyzed. Abstract: This paper investigates blast resistance and residual strength of concrete-filled steel tube (CFST) columns under close-range blast loads. A total of 8 CFST columns, including 4 with circular cross sections and 4 with square cross sections, were tested under close-range blasts. LVDTs were used to record displacement histories and pressure sensors were used to measure pressure histories. The influence of explosive charge weight, steel tube thickness and cross section geometry on dynamic response of CFST columns was analyzed and failure modes of CFST columns were also investigated. Following the blast tests, an experimental study was conducted to investigate residual strength of blast-damaged CFST columns. It was found that the CFST columns were still able to retain a large portion of their axial load capacities even after close-range blast events.